A design of machine tool for switchable multi-NC systems test - Zhang, Yun; Lin, Haifeng; Zeng, Yang; Fei, Ya (Journal of physics. Conference series, 2020)
A machine tool with 4 kinds of NC systems have been designed. The systems can control the same transmission mechanism and switch freely. The machine tool mainly used for the test of NC system function and performance. At present, the machine tool has been tested. The results show that the functions and performances of different NC systems can be compared and tested under the same condition of transmission mechanism.